Serum chloride and serum sodium derangements in children on prolonged furosemide therapy and their effect on diuretic response - Nanies Mohamed Salah EL Din Soliman; Alyaa Amal Kotby; Menatallah Ali Shabaan; Esraa Matarawy Eid (SpringerOpen, 2022)
Abstract Background Electrolyte disturbances are not uncommon in patients on chronic furosemide therapy. We hypothesized that serum chloride (Cl) and serum sodium (Na) abnormalities may occur in children on prolonged furosemide therapy affecting the diuretic response in these children. Methods The study included 45 children, with congenital left to right shunts causing chronic congestive state which necessitated chronic furosemide therapy. Patients in need to an increase of their furosemide dose were recruited in the study. We assessed serum Cl and serum Na as well as parameters of diuretic responsiveness; net fluid output and change in body weight/40 mg furosemide, and change in urinary Na/K ratio. These parameters were assessed initially and at day 3 after increasing furosemide dose. Results According to serum levels of Cl and Na, patients were divided into four groups: isolated hyponatremia (15 patients, 33.3%), isolated hypochloremia (9 patients, 20%), combined hypochloremia and hyponatremia (12 patients, 26.7%), and normal serum electrolytes (9 patients, 20%). Patients with combined hyponatremia and hypochloremia and those with isolated hypochloremia showed minimal clinical and radiological signs of decongestion as well as lowest changes in urinary Na/K ratio, fluid output and weight change/40 mg furosemide on augmenting the diuretic dose, unlike the hyponatremic patients who had near normal parameters with no evidence of diuretic resistance. Conclusion Both hypochloremia and hyponatremia are common in patients on prolonged furosemide therapy. Hypochloremia is associated with a poor diuretic response, unlike isolated hyponatremia which does not seem to affect the diuretic response. Concomitant occurrence of hyponatremia and hypochloremia is associated with poor diuretic response as well which can be worse than that seen in isolated hypochloremia.